Adverse childhood experiences among California student pharmacists - Shawn R. Smith, PharmD, APh; Leslie Banuelos, PharmD; Nalea Trujillo, PharmD; Destiny Farihi, PharmD; Stephanie Lee, PharmD; Sharon Truong, PharmD; Tracy Ly, PharmD; David Dadiomov, PharmD, BCPP; Nancy Kawahara, PharmD, MS; Paul Gavaza, PhD (American Association of Psychiatric Pharmacists, 2024)
Introduction Adverse childhood experiences (ACEs) are associated with higher mental and physical illness and substance use disorders in adulthood. However, little is known about the prevalence of ACEs among student pharmacists and the factors associated with exposure. Our objective was to determine the prevalence of ACEs, resilience, and maladaptive coping strategies among student pharmacists in California. Methods Student pharmacists from 14 California pharmacy schools completed a 24-item online survey in 2020. This survey instrument comprised the ACEs questionnaire and collected data on the students' demographic characteristics, coping strategies, and resilience. Results Most respondents were Asian/Pacific Islander (n = 186, 61.0%), female (n = 216, 70.8%), and aged between 25 and 31 years (n = 154, 50.7%). Many (n = 137, 44.9%) students had more than 1 ACE exposure; 66 students (21.6%) had more than 3 ACEs. Many students indicated that they were diagnosed or suspected to be diagnosed with a mental health condition (n = 105, 34.4%) and agreed/strongly agreed that they struggled to manage the workload of pharmacy school (n = 119, 39.9%). Respondents with higher ACE scores (> 3) were more likely to report struggling with managing the workload of pharmacy school, have or suspect having a mental health condition, drink alcohol in the last 12 months, and/or have multiple sexual partners than students with lower ACE scores. Discussion More than 1 in 5 student pharmacists in this study were exposed to more than 3 ACEs. The student pharmacists' ACE exposure was associated with higher likelihood of mental health conditions and high-risk health behaviors. Further studies are needed to investigate this topic among student pharmacists.